Historical archaeology in the twenty-first century : lessons from Colonial Williamsburg - Edwards-Ingram, Ywone; Edwards-Ingram, Ywone; Edwards, Andrew C.; Edwards, Andrew C. (Florida scholarship online, 2021)
This volume offers an in-depth look at historical archaeology, public history, and reconstruction in Williamsburg through a comprehensive range of sites, topics, and analyses. Uniquely combining a historical landscape and a large town museum complex, Colonial Williamsburg has deeply influenced the discipline for 100 years through one of the nation's longest continuously running archaeological conservation programs. The book illuminates the town's history as an early capital of the Virginia Colony and home to the College of William & Mary